Effect of machining parameters on cutting force during micro-turning of a brass rod. Issue 16 (10th December 2019) - Singh, Surinder; Ghai, Viney; Agrawal, Anupam; Singh, Harpreet
ABSTRACT: Micro-needles finds abundant applications in the field of medicines, nanodevices and as a tool for µ-EDM to study single spark energy. Fabrication of such micro-needles with high accuracy and precision is a challenging task. In this work, an attempt has been made to manufacture a brass rod by micro-turning to a diameter of 100 µm. Effects of cutting speed and feed rate on feed-force, cutting-force, machining-force, surface-roughness, power, and specific cutting force have been studied to optimize the process of fabricating a brass micro-needle with a smoother surface. SEM, EDS, and AFM have been performed to study cutting behavior along with the fracture behavior of fabricated micro-needle. The cutting force behavior was non-linear and was in accordance with the available literature even at micro-level. In addition to this, the fabricated micro-needles were etched using hydrogen peroxide (H2 O2 ) to fabricate a sharp-pointed needle having a diameter of ≤ 10 µm. Fabricated µ-turned sharp micro-needles may be further used as a tool to study single spark energy in the µ-EDM process. Additionally, crater depth, diameter, tool wear rate (TWR) and material removal rate (MRR) have been calculated for the single spark of the µ-EDM process using fabricated micro-tool.